HANDLING OF MEDICAL RECORD DOCUMENTS IN FACING DATA DIGITIZATION AT MITRA SEHAT SITUBONDO HOSPITAL - Rusdi, Achmad Jaelani; Bulgis, Malikal; Yosin, Kresensia Dasilva (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Hospitals as health service providers are responsible for ensuring the storage of medical records in accordance with regulations, both in conventional and electronic form. At Mitra Sehat Situbondo Hospital, the process of transitioning from conventional to electronic medical records is ongoing, but has not yet been fully implemented. Some of the obstacles faced include delays in digitalization and no clear operational procedures (SOP). This research aims to evaluate the management of medical records in support of digitalization, using a qualitative descriptive approach involving observation and interviews. The research results show that the use of RME at Mitra Sehat Hospital has only been implemented in outpatient settings, while scanning and digitizing medical records is not yet optimal. Digitalization of conventional medical record files is carried out through a scanning and retention process to reduce the accumulation of files in the filing unit. Storage efficiency and security of physical documents that indicate damage, loss and natural factors can be maintained with digital files. Through this research, it is hoped that Mitra Sehat Hospital can design features that support media transfer to ensure consistent medical records and ensure an efficient data migration process.